Bosnia and Herzegovina : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Bosnia and Herzegovina has enjoyed rapid growth and price stability in recent years, but stronger policy ownership, improved policy coordination, and meaningful progress in structural reform are needed to provide the basis for sustained, private sector-led growth. Ensuring the sustainability of public finances in the face of emerging spending pressures and still uncertain domestic liabilities is required. Improving fiscal governance and coordination, reducing financial sector vulnerabilities, and strengthening the private sector while improving competitiveness and the external position is required.